Ekstraksi Lead Pacu Jantung dengan Kabel Seluruhnya Tertarik ke dalam Ventrikel Kanan - Wishnu Aditya; Yoga Yuniadi; Erika Maharani; Farial Indra; Edrian Zulkarnaen; Yandi Arifiudin (Jurnal Kardiologi Indonesia, 2012)
We are reporting a case of lead extraction from a woman who has been implanted permanent peacemaker (PPM), and later has a complication of a local site infection and infective endocarditis. She had multiple local debridement procedures, generator removal, and multiple cable amputation. Her PPM wire was free-floating inside the right ventricle (RV). Lead extraction was done successfully using a snare catheter and a long sheath.